Gynura procumbens Adventitious Root Ameliorates Oxidative Stress and has Cytotoxic Activity Against Cancer - Ummi Zubaidah; Sugiharto; Muhammad Idrissa P. Siregar; Ufairanisa Islamatasya; Nabilatun Nisa; Anjar Tri Wibowo; Yosephine Sri Wulan Manuhara (BIO Integration, 2024)
Background: Lead exposure is a growing concern in recent public health because lead acts as an oxidant, causing oxidative stress. In this context, the administration of exogenous antioxidants is imperative. Our preliminary study revealed that Gynura procumbens leaf and root contain phenolics and flavonoids. The current study aims to determine the potency of G. procumbens adventitious root (ARGp) in preventing oxidative stress caused by lead exposure and the potential as an anti-cancer agent. Methods: ARGp was induced from leaf explant, propagated inside a bioreactor, and macerated by methanol. Balb/C mice were used in an in vivo study and divided into 5 groups, as follows: P1 (distilled water); P2 (Pb 100 mg/L); P3 (ARGp-100 mg/L + Pb 100 mg/L); P4 (ARGp-200 mg/L + Pb 100 mg/L); and P5 (ARGp-300 mg/L + Pb 100 mg/L). Hematologic parameters, the level of lipid peroxidation, and GPx-4 antioxidant gene expression were subsequently recorded. Results: Administration of ARGp significantly increased the hematocrit and mean corpuscular volume but did not significantly increase the mean corpuscular hemoglobin compared to lead exposure (P2). In contrast, ARGp significantly lowered the mean corpuscular hemoglobin concentration (MCHC) and white blood count compared to P2. ARGp significantly decreased liver and kidney lipid peroxidation but not in the serum. These findings are consistent with the ability of ARGp to enhance endogenous antioxidant gene expression, especially GPx-4 . Furthermore, ARGp exhibited a cytotoxic effect on the hepatoma (Huh7it) cell line with an IC 50 44.65 mg/L. Conclusion: ARGp possesses antioxidants by restoring hematologic damage, lowering lipid peroxidation, and increasing antioxidant gene expression, as well as anti-cancer activity.